2007
DOI: 10.1590/s0482-50042007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Disautonomia: um conceito emergente na síndrome da fibromialgia

Abstract: Recebido em 30/03/07. Aprovado, após revisão, em 15/08/07. Declaramos a inexistência de conflitos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
5
0
3
Order By: Relevance
“…The opposite occurs during N-REM sleep, where there is a lower activation of SNS and greater activation of the PNS. (18) In addition, there is a relationship with the results found in this study, where there was a decrease in SNS and a significant increase in Deltas waves, corroborating with the physiological processes already described in the literature. It's reported that sleep is also an important modulator of cardiovascular function, where there is a temporal association between physiological sleep and the occurrence of vascular events, cardiac arrhythmias and sudden death.…”
Section: Discussionsupporting
confidence: 91%
“…The opposite occurs during N-REM sleep, where there is a lower activation of SNS and greater activation of the PNS. (18) In addition, there is a relationship with the results found in this study, where there was a decrease in SNS and a significant increase in Deltas waves, corroborating with the physiological processes already described in the literature. It's reported that sleep is also an important modulator of cardiovascular function, where there is a temporal association between physiological sleep and the occurrence of vascular events, cardiac arrhythmias and sudden death.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that autonomic dysfunction is an important participant mechanism in the genesis and maintenance of the symptoms and comorbidities of fibromyalgia. (26) In addition, the aforementioned study cited a limitation that one of the exclusion criteria used consisted of not admitting patients to the sample who used other complementary therapies, and may have approached patients different from the patients we approach in our clinics every day. Regarding craniosacral manipulative therapy, in addition to Guillermo et al (25) , two other studies in this Buttagat et al (2009) TMT provided a greater increase in the high frequency band, systematic review used the technique: Fornari, Carnevali and Sgoifo (15) and Girsberger et al (20) Fornari, Carnevali and Sgoifo (15) , used a sample composed of healthy women with a mean age of 20 ± 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…A fibromialgia é uma síndrome reumática complexa caracterizada por sítios dolorosos sensíveis à palpação, conhecidos como Tender Points 5 , bem como dores musculares esqueléticas difusas e crônicas sem evidência reumática e inflamatória [6][7] , estando associada [8][9] a outras sintomatologias decorrentes do envolvimento do sistema nervoso central, endócrino e psicológico. 10 Geralmente os portadores da fibromialgia apresentam sintomas característicos que surgem por volta dos 29 aos 37 anos de idade 11 , como dor difusa e crônica que se inicia no ombro ou coluna lombar e dissemina-se pelo corpo. Apresentam ainda fadiga generalizada, rigidez matinal, formigamento, sensação de edema, diminuição da aptidão cardiorrespiratória, dispnéia, cefaléia (tensional e enxaqueca) 12 , ansiedade, distúrbios do sono 13 , insônia crônica, síndrome do intestino e bexiga irritados 14 , secura nos olhos e boca, hiperalgesia e alodínia, tonturas e disfunções cognitivas 15 , distúrbios de humor e depressão, sendo esta última a mais comum dentre os pacientes.…”
Section: Revisão Da Literaturaunclassified
“…3,16 Para Bennet apud Giu et al 16 a fibromialgia é a associação de microtraumas musculares [5][6] com distúrbios do sono isto porque em decorrência do sono não reparador pode ocorrer um desbalanço no ritmo biológico. [11][12] Em países industrializados a fibromialgia afeta cerca de 3 a 5% de toda população mundial 19 ficando atrás apenas da osteoartrite degenerativa. [14][15] Dentre os pacientes acometidos, 49 a 80% apresentaram agravos ou alterações no quadro psicológico.…”
Section: Revisão Da Literaturaunclassified